Calibration and Standardisation of Synchrotron Radiation Circular Dichroism and Conventional Circular Dichroism Spectrophotometers. Issue 4 (2003) - Miles Miles, Andrew J. Andrew J.; Wien Wien, Frank Frank; Lees Lees, Jonathan G. Jonathan G.; Rodger Rodger, A. A.; Janes Janes, Robert W. Robert W.; Wallace Wallace, B. A. B. A.
Abstract : Synchrotron radiation circular dichroism (SRCD) is an emerging technique in structural biology with particular value in protein secondary structure analyses since it permits the collection of data down to much lower wavelengths than conventional circular dichroism (cCD) instruments. Reference database spectra collected on different SRCD instruments in the future as well as current reference datasets derived from cCD spectra must be compatible. Therefore there is a need for standardization of calibration methods to ensure quality control. In this study, magnitude and optical rotation measurements on four cCD and three SRCD instruments were compared at 192.5, 219, 290 and 490 nm. At high wavelengths, all gave comparable results, however, at the lower wavelengths, some variations were observable. The consequences of these differences on the spectrum, and the calculated secondary structure, of a representative protein (myoglobin) are demonstrated. A method is proposed for standardising spectra obtained on any CD instrument, conventional or synchrotron‒based, with respect to existing and future databases.